SISTEM REKRUTMEN, SELEKSI DAN PENEMPATAN KEPALA SEKOLAH MENENGAH PERTAMA NEGERI PADA DINAS PENDIDIKAN KOTA BANDA ACEH - Baihaqi .; Khairuddin .; Muhammad Husen (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2012)
Abstract: Recruitment, selection, and replacement of the principal conducted in accordance with competence can improve the quality of education management. This research aimed at figuring out the description of process of recruitment, selection, and replacement and also the obstacles in recruitment, selection and replacement of State Junior High School principal at Education Agency of Banda Aceh. This research employed descriptive qualitative method. Data was collected by using observation, interview, and documentation technique. Subject of the research was principal and teacher at State Junior High School. The result of the research showed that: first, the recruitment process, the Education Agency prepared a recruitment program comprising of implementation and technical guidance of recruitment implementation for the candidates of principal, then there was an official announcement from the Education Agency. Second, the selection process on the principal candidates comprised of administrative selection carried out through the assessment of the completeness of documents and academic selection carried out through the assessment of the leadership potential and initial mastery of toward competence of principal. Third, the replacement process of principal candidates was conducted because there was principal vacancy caused by the transfer, retirement, and dismissal. Fourth, the obstacles in recruitment, selection, and replacement of the principalwere lack of interest of the teachers to run for principal and lack of the budget for principal recruitment. It can be concluded that the recruitment, selection, and replacement of State Junior High School principal are still ineffective and inefficient.Keywords: Recruitment, Selection, and Replacement of Principal